Divine Emotions: On the Link Between Emotional Intelligence and Religious Belief - Łowicki, Paweł (J Relig Health, 2016)
There have been only few attempts to explore the relationship between emotional intelligence (EI) and religiosity. However, none of them included measures of ability EI. In two studies, we investigated the potential associations between various aspects of religious belief and ability and trait EI. In Study 1 (N = 240), we found that ability EI was positively associated with general level of religious belief. Study 2, conducted among Polish Christians (N = 159), replicated the previous result on the connection between ability EI and religion. Moreover, both trait and ability EI were negatively correlated with extrinsic religious orientation and negative religious coping. Additional analysis showed that extrinsic orientation mediated the relationship between ability EI and religiosity.